2014
DOI: 10.1186/1471-2369-15-128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of double filtration plasmapheresis with immunoadsorption therapy in patients with anti-glomerular basement membrane nephritis

Abstract: BackgroundDouble filtration plasmapheresis (DFPP) and (IA) are both used to clear antibody. However, the clinical efficacy and safety of DFPP in patients with anti-glomerular basement membrane (anti-GBM) disease are unclear.MethodsThe 28 enrolled patients diagnosed serologically and pathologically with anti-GBM disease from 2003 to 2013 included 16 treated with DFPP and 12 with IA, with all patients administered immunosuppressive agents. DFPP consisted of an EC50W filter for plasma separation and an EC20W filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
3
22
0
3
Order By: Relevance
“…Although plasmapheresis is an invasive procedure and might be associated with side effects, it is associated with a favourable safety profile, regardless of the original indication. [8][9][10] Our study confirmed a very good safety profile of this method.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although plasmapheresis is an invasive procedure and might be associated with side effects, it is associated with a favourable safety profile, regardless of the original indication. [8][9][10] Our study confirmed a very good safety profile of this method.…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, the two largest series to date both comprised five patients with PBC, both reporting significant improvement of pruritus. Although plasmapheresis is an invasive procedure and might be associated with side effects, it is associated with a favourable safety profile, regardless of the original indication . Our study confirmed a very good safety profile of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [75] analyzed the 28 enrolled patients diagnosed serologically and pathologically with anti-GBM disease from 2003 to 2013 in whom 16 treated with DFPP and 12 with IA, A double volume of plasma was processed, and each patient received a 30-40 g human albumin supplement during each session. IA consisted of 10 cycles per session, with 8-10 sessions performed daily or every other day and each session regenerating 30-60 L of plasma.…”
Section: Rebound Antibody Reactionmentioning
confidence: 99%
“…Die Daten zur Prognose von ANCA-positiven Patienten mit Anti-GBM-Erkrankung sind uneinheitlich -es wurden sowohl eine höhere als auch niedrige Wahrscheinlichkeit eines Erhalts der Nierenfunktion bei positivem ANCA berichtet [3,15,44]. Ergebnisse einer Kohortenstudie an 28 Patienten konnten zeigen, dass eine Immunadsorption im Vergleich zu einer Doppelfiltrationsplasmapherese nicht zu einem besseren therapeutischen Ergebnis (Entfernung von Anti-GBM-Antikörper) führte, aber mit einem höheren Gesamt-IgG-Verlust assoziiert war [75]. Die Leitlinien der KDIGO (Kidney Disease: Improving Global Outcomes) empfehlen, bei Patienten mit akuter Anti-GBM-Erkrankung zusätzlich zur Immunsuppression mit CYC (oral 2-3 mg/kg plus Prednisolon) eine Plasmapherese als First-Line-Therapie durchzuführen, bis die Anti-GBM-Antikörper im Serum nicht mehr nachweisbar sind [55].…”
Section: » Entscheidend Für Dieunclassified